2006
DOI: 10.1253/circj.70.1275
|View full text |Cite
|
Sign up to set email alerts
|

Association Between A/C1166 Gene Polymorphism of the Angiotensin II Type 1 Receptor and Biventricular Functions in Patients With Acute Myocardial Infarction

Abstract: cute myocardial infarction (AMI) is characterized by loss of contractile tissue and changes in ventricular geometry. 1 The presence of congestive heart failure or left ventricular (LV) systolic dysfunction is probably the most important risk factor in patients with AMI. 2 The development of right ventricular (RV) dysfunction has been reported following LV myocardial infarction (MI), 3,4 and is also associated with increased risk of shock, arrhythmia, and death. 5,6 After MI, the process of LV remodeling begins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…This allele distribution showed a similarity to the respective frequencies reported in the single nucleotide polymorphism database using different European Caucasian populations or samples of the Centre d’Etude du Polymorphisme Humain (65–75 and 25–35% for the A and C alleles, respectively). Considerable interethnic variation in the frequencies of this polymorphism has been demonstrated, with the –1166C allele being rarer in African American and Asian populations (94–97 and 3–6% for the A and C alleles, respectively, single nucleotide polymorphism database) compared with European Caucasian groups [20], which is consistent with our findings. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This allele distribution showed a similarity to the respective frequencies reported in the single nucleotide polymorphism database using different European Caucasian populations or samples of the Centre d’Etude du Polymorphisme Humain (65–75 and 25–35% for the A and C alleles, respectively). Considerable interethnic variation in the frequencies of this polymorphism has been demonstrated, with the –1166C allele being rarer in African American and Asian populations (94–97 and 3–6% for the A and C alleles, respectively, single nucleotide polymorphism database) compared with European Caucasian groups [20], which is consistent with our findings. …”
Section: Discussionsupporting
confidence: 92%
“…However, most studies did not find a role for the AT1R polymorphism in the determination of LV size and performance, both in healthy individuals and in patients with coronary artery disease [15,16,17,18,19,20]. Hamon et al [21] showed that subjects homozygous for the AT1R CC mutation did have a lower EF than those with at least a single A allele (AC + AA).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported a positive association [12–14], while others could not find any association [10, 11, 28, 29]. …”
Section: Discussionmentioning
confidence: 99%
“…24,25) A number of initial studies attempted to address the possibility that polymorphisms at various candidate genes might be associated with the pathogenesis of CAD and some concluded there was a significant association between them. For example, polymorphisms in renin-angiotensin system gene polymorphisms (angiotensin-type receptor genes, angiotensin II converting enzyme genes) are well known to be associated with hypertension, 26) CAD [27][28][29][30][31] and MI, [32][33][34] though dissenting opinions still exist.…”
Section: Discussionmentioning
confidence: 99%